Enforced Disappearance of Persons: a Key Feature of the Cold War from Argentina to Central America - Rostica , Julieta Carla (2025)
The Cold War was a global ideological war that was settled with the use of political violence in Third World countries. The one that specifically characterized Latin America was the forced disappearance of people. Its massive, systematic and widespread use was such that it forced the international community to create instruments for its prevention and punishment. To demonstrate this, we compare the forced disappearance of persons in the most illustrative and contrasting national cases, such as Argentina, Guatemala, Honduras and El Salvador. The aim is to demonstrate their relative relevance to stimulate future research that seeks a transnational explanation centered on the Third World.